A Study on Optimizing Civil Servant Performance: The Role of Employee Engagement and the Merit System through Competency Development at the National Unity and Political Agency of North Kalimantan Province - Romyansyah, Romyansyah; Juliana, A (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
This study aims to analyze the influence of Employee Engagement and the Merit System on improving the performance of Civil Servants (ASN), with Competency Development as a mediating variable, at the National Unity and Political Agency in North Kalimantan Province. The research employs a quantitative approach using Partial Least Square-Structural Equation Modeling (PLS-SEM) for analysis. Data were collected through questionnaires distributed to 60 respondents selected using purposive sampling. The findings indicate that employee engagement and the merit system do not have a direct significant impact on improving ASN performance. However, both variables exert an indirect significant influence through competency development. Competency development itself has a direct and significant effect on performance improvement, making it a key factor in enhancing the capacity and productivity of civil servants. Employee engagement positively contributes to competency development, indicating that employee involvement plays a crucial role in encouraging active participation in training and development programs. Additionally, the merit system also positively affects competency development, suggesting that implementing a fair and performance-based system can motivate employees to enhance their skills